2021
DOI: 10.1093/jtm/taab046
|View full text |Cite
|
Sign up to set email alerts
|

Trends of the global, regional and national incidence of malaria in 204 countries from 1990 to 2019 and implications for malaria prevention

Abstract: Background Malaria is a life-threatening disease worldwide, but lacks studies on its incidence at the global level. We aimed to describe global trends and regional diversities in incidence of malaria infection, to make global tailored implications for malaria prevention. Methods We used the data from the Global Burden of Disease Study 2019. The age-standardized incidence rate (ASR) and absolute number of malaria episodes showed the epidemic status of malaria infection. The estimated annual perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 28 publications
0
35
0
1
Order By: Relevance
“…Most previous studies reported province or regional prevalence of HBV infection in China, such as Tianjin (3.8%) [29] , Zhejiang (5.9%) [30] and Taiwan (12.4%) [31] . At national level, there were four national epidemiological surveys on investigating HBV infection in the general population in China, which was conducted in 1979 [22] , 1992 (including people aged 1-59 years) [32] , 2006 (including people aged 1-59 years) [ 33 , 34 ], and 2014 (including people aged 1-29 years) [9] , respectively. After 2006, there were no national representative survey conducted in the general population aged 1-59 years, especially for adults.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most previous studies reported province or regional prevalence of HBV infection in China, such as Tianjin (3.8%) [29] , Zhejiang (5.9%) [30] and Taiwan (12.4%) [31] . At national level, there were four national epidemiological surveys on investigating HBV infection in the general population in China, which was conducted in 1979 [22] , 1992 (including people aged 1-59 years) [32] , 2006 (including people aged 1-59 years) [ 33 , 34 ], and 2014 (including people aged 1-29 years) [9] , respectively. After 2006, there were no national representative survey conducted in the general population aged 1-59 years, especially for adults.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the estimated annual percentage change (EAPC), a summary and widely used indicator to show the trend and annual change over a specified time interval [ 21 , 22 ]. There are many methods to estimate the annual percentage change [23] , [24] , [25] , [26] , [27] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations